Alcohol drinking leads to sex-dependent differentiation of T cells - Sturm, Ramona; Haag, Florian; Bergmann, Christian B.; Marzi, Ingo; Relja, Borna (European journal of trauma and emergency surgery, 2025)
Objective Global per capita alcohol consumption is increasing, posing significant socioeconomic and medical challenges also due to alcohol-related traumatic injuries but also its biological effects. Trauma as a leading cause of death in young adults, is often associated with an increased risk of complications, such as sepsis and multiple organ failure, due to immunological imbalances. Regulatory T cells play a crucial role in maintaining immune homeostasis by regulating the inflammatory response. Since it is crucial to understand the effects of alcohol in healthy volunteers, in order to refer findings from trauma cohorts, this study investigates the time- and dose-dependent modulation of CD4+ lymphocytes and their subsets following acute alcohol consumption, considering both general and sex-specific variations. Methods Twelve female and ten male healthy volunteers consumed twelve alcohol mixed drinks over four hours to achieve a blood alcohol level of 1.0‰. Blood samples were collected before and at various time points (2, 4, 6, 24 and 48 h) post-consumption for flow cytometric analyses of the phenotype and activation makers CD4/CD25/CD127 of CD4+ T cells and their subtypes. Results CD4+ lymphocytes significantly decreased at 4 h and increased at 6 h post-alcohol consumption. Naïve CD25−CD127+ T cells significantly decreased from 2 to 24 h in women and 2 to 48 h in men, while CD25+CD127+ effector T cells significantly increased during the same period. Natural CD25+CD127− regulatory T cells increased significantly at 4 and 6 h, with a higher increase in men. Induced regulatory T cells (CD4+CD25highCD127−) significantly increased at 2 h for all volunteers, with lower proportions of natural and induced regulatory T cells in women. Conclusions Acute alcohol consumption induces immune modulation persisting for days, impacting T cell subsets differently in men and women. The prolonged modulation in men may contribute to slightly poorer clinical outcomes, emphasizing the need to consider these effects in trauma patients with acute alcohol intoxication.